2018
DOI: 10.1177/0961000618790629
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between emotional intelligence, library anxiety, and academic achievement among the university students

Abstract: Emotional intelligence has a strong link with academic anxieties. It is apparent from the published literature that a student with high emotional intelligence would face low academic anxiety and vice versa. Similarly, library anxiety, which is an academic anxiety, also affects students’ academic performance. Library anxiety of students may increase or decrease along with their ability to understand and manage their own emotions and those of others. However, there is a dearth of literature on the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 46 publications
1
25
0
5
Order By: Relevance
“…In the present study, the effect of emotional intelligence was more on high anxious learners rather than the learners with low level of anxiety especially in intrapersonal abilities and adaptability as subscales of emotional intelligence and emotional intelligence in general. Therefore, this result contradicts Jan et al's (2018) findings.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In the present study, the effect of emotional intelligence was more on high anxious learners rather than the learners with low level of anxiety especially in intrapersonal abilities and adaptability as subscales of emotional intelligence and emotional intelligence in general. Therefore, this result contradicts Jan et al's (2018) findings.…”
Section: Discussionmentioning
confidence: 59%
“…For example, when a teacher shows positive or negative reactions towards learners' achievement or failure, his or her emotions are aroused (Nias, 1996). Jan et al (2018) showed in their research that there is a negative relationship between emotional intelligence and language anxiety. In fact, when a learner develops his or her emotional intelligence, he or she can not only more manage his or her own emotions and those of the others but also can be more motivated in the development of academic achievement in comparison to the learners with low emotional intelligence (Jan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the observation of an almost metonymic relationship between the object and the person who handles it (the book and the librarian) has been the subject of several North American studies that highlight the embodiment of the book in a highly-literate, pedagogical female figure, more supervisory than benevolent. Her attitude is felt to be hypercritical toward young people in general, and can create anxiety particularly in boys [20,52]. While these interactions are not conscious or deliberate, they nevertheless play a central role in discouraging and driving away individuals and groups poorer in cultural capital and less docile with the respect to the norms that govern the library apparatus [5], sheltering it from more restless groups.…”
Section: Relations: the Origin And Engine Of Social Tiesmentioning
confidence: 99%
“…The group at the library fulfils a social function, just as it contributes to weakening among young people the barriers of sex symbolized by a clear division between reflection and abstraction, on the one hand, and a practical relationship with the world on the other. [52] It can also provide a scene for experimenting with new emotions because it allows boys and girls to measure their respective efforts in intellectual work, to observe these efforts palpably in the bodies of others, and to generate emotions akin to the sentiment of solidarity and kindness. [42] One of the forces that seems to be at work in the acculturation of young adults in the library is group-driven mimicry.…”
Section: The Noisy Clusters Of Youth: Better Outside Than In?mentioning
confidence: 99%